HUBUNGAN MINDFULNESS DAN STRES AKADEMIK PADA MAHASISWA TAHUN PERTAMA - Ester Shavanya A; Arthur Huwae (Jurnal Psimawa : Diskursus Ilmu Psikologi dan Pendidikan, 2026)
First-year students often experience academic stress due to academic demands and adjustment to a new college environment. Limited self-regulation skills make them more prone to academic pressure. This study aims to examine the relationship between mindfulness and academic stress among first-year students. The research used a quantitative correlational method involving 56 participants aged 17–19 years, selected through incidental sampling, using the Five Facet Mindfulness Questionnaire for mindfulness and Educational Stress Scale for Adolescent (ESSA) for academic stress. The Pearson correlation results showed a significant negative relationship between mindfulness and academic stress (r = -0.309; p < 0.05). The findings indicate that mindfulness reduces academic stress, suggesting the need for mindfulness training to help first-year students adapt and maintain mental well-being.